θ-Role Assignment in Derived Nominals - Emonds, Joseph (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1986)
AbstractChomsky and Stowell attribute an asymmetry in noun and verb complement systems to how these categories assign Case. Here, Case assignment is dependent on structural configurations that θ-role theory determines; it is the latter which explains asymmetries in the noun and verb complement systems.Several predicate attribute and Vk (clausal) complement types are examined, and all confirm the θ-role theory in which V can assign θ-roles directly to sisters of any phrasal type, while N and A can assign θ-roles only "indirectly," to Ymax appearing in PP structures. This predicts the new patterns examined here, as well as the asymmetry in how objects of verbs and derived nominals are syntactically realized.